Modified diene polymer and preparation method thereof
By introducing low molecular weight polybutadiene with terminal alkoxysilane groups as a modifier into the polybutadiene rubber composition, and polymerizing in the presence of a catalyst complex, the problem that polymers in the prior art can be The problems of insufficient processability and wear resistance are achieved by achieving better filler distribution and wear characteristics.
Patent Information
- Application Number
- CN201980103035.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-20
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2039-12-20
AI Technical Summary
The prior art has shortcomings in improving the processability and wear resistance of polybutadiene rubber compositions, especially in terms of filler distribution and wear characteristics in polymer matrix.
By preparing low molecular weight polybutadiene containing terminal alkoxysilane groups as a modifier and polymerizing in the presence of a catalyst complex, the degree of branching and filler distribution of the polymer is improved.
The wear resistance and processability of the rubber composition are significantly improved, the filler distribution in the polymer matrix is improved, and the Mooney viscosity and content of high molecular weight fractions are reduced.
Smart Images

Figure BDA0003697664510000041 
Figure BDA0003697664510000131 
Figure BDA0003697664510000132
Abstract
Description
Technical Field
[0001] The present invention relates to the synthetic rubber industry and, in particular, to the production of polymers used in the manufacture of tires and other rubber products. In particular, the present invention relates to diene polymers modified by low molecular weight polybutadiene containing terminal alkoxysilane groups and methods for their production.
[0002] Technical results include the preparation of polydienes with improved processability and filler distribution in a polymer matrix, wherein rubber compositions based on said polydienes significantly improve the wear resistance (Shopper-Schlobach wear volume loss, mm 3 ). Furthermore, the modified diene polymer obtained according to the invention is characterized by a Mooney viscosity of 40 to 50 Mooney units, a content of high molecular weight fraction (HMF 1 million amu) of not more than 3.5% by weight, a branching index characterized by the mechanical loss tangent tgδ (1200%) (measured by thermogravimetry according to ASTM E1131, ISO 11358) of 4.0 to 6.0, and a polydispersity index of 2.1 to 2.5% by weight, a content of 1,4-cis units of more than 96% by weight. Background Art
[0003] It is known that the use of 1,4-cis-polybutadiene allows obtaining rubber compositions having low hysteresis loss values and high durability. However, these rubbers are characterized by poor processability due to the high viscosity of the polymer products obtained. The prior art discloses methods for using liquid / low molecular weight rubbers as additives at the rubber mixing stage to improve the processability of polybutadiene rubber compositions.
[0004] Patent application GB964931A (OLIVER WALLIS BURKE, July 29, 1964) discloses polymer blends and methods for producing the same, namely, using liquid diene polymers and / or their sulfides mixed with 1,4-polybutadiene obtained by solution polymerization on a metallocene catalyst system at the rubber mixing stage to improve processability. According to the method, diene polymerization is carried out in the presence of an organic lithium compound as a catalyst.
[0005] However, data on the properties of the rubber composition obtained are not presented in this application, and moreover the microstructure of the rubber obtained comprises cis-isomers in an amount of less than 96%, which results in an increase in the wear capacity of the rubber.
[0006] It is well known to use liquid diene polymers as components of rubber compositions. Patent EP2082899 (CONTINENTAL AG (DE), May 18, 2011) describes a method for producing a rubber compound whose formulation contains 5 to 50 parts by weight of a liquid low-viscosity polymer. The resulting mixture exhibits improved elasticity at low temperatures and improved tensile modulus at 300% elongation.
[0007] In the inventor's certificate SU1028681A (YAROSLAVSKIJ POLT INST (SU), July 15, 1983) it is shown that the use of low molecular weight epoxidized cis-polybutadiene in the formulation of rubber compounds based on SBR (synthetic butadiene rubber) makes it possible to significantly improve the fatigue resistance of the rubber during stretching.
[0008] Application US5430095 A (KURARAY CO (JP), July 4, 1995) discloses a method for improving the properties of a rubber composition, i.e., processability and distribution of fillers (i.e., carbon black), by using a low molecular weight diene polymer, in particular, an isoprene polymer, produced using a lithium-containing catalyst having functional hydroxyl or amino groups as an additive. According to the document, the introduction of a low molecular weight polymer as an additive at the rubber mixing stage helps to improve the processability of the rubber composition and improves fatigue resistance when the rubber is stretched. However, the selected introduction method does not lead to an improvement in the properties of the main polymer, and an increase in the amount of low molecular weight diene polymer used during rubber mixing leads to a deterioration of physical and mechanical properties.
[0009] Patent US6437205B1 (BRIDGESTONE CORP (JP), August 20, 2002) describes the use of a mixture of low molecular weight polybutadiene and high molecular weight polybutadiene obtained using a neodymium catalyst system as a rubber composition for tire treads. According to this method, the rubber composition obtained is characterized by good wet road grip, high rolling resistance and good physical and mechanical properties, in particular, tensile stress at break and elastic modulus.
[0010] However, taking these polybutadienes in a 50:50 ratio increases the cost of the final product due to the high cost of low molecular weight polymers. The resulting polymer blend has a low content (ie 90%) of 1,4-cis units, which causes high wear of the rubber composition.
[0011] The process for preparing polybutadiene disclosed in patent US7112632 (POLIMERI EUROPA SPA (IT), September 26, 2006) is the closest to the essence of the present invention. According to this process, the process for preparing polybutadiene comprises: (a) polymerizing butadiene; (b) treating the polymer solution obtained after completion of stage (a) with a coupling agent selected from the group consisting of: (i) unsaturated natural oils; (ii) butadiene and / or isoprene oligomers; (iii) copolymers of butadiene and / or isoprene with vinyl aromatic monomers; the unsaturation present in compounds (i) to (iii) is at least partially replaced by a group selected from epoxides, anhydrides and esters; (c) recovering the low-branched polybutadiene obtained after completion of stage (b). According to this patent, a low-branched polymer is obtained.
[0012] Branched polymers are known for achieving good processability of rubber compositions. The patent contains no information on the extent of filler distribution in the polymer matrix and improving the wear and processability of the obtained polymer. Summary of the invention
[0013] The object of the present invention is to improve the processability and technological effectiveness of polydiene polymers and thereby improve the filler distribution in the polymer matrix and the wear resistance of rubber compositions based on these polydiene polymers.
[0014] In order to achieve the above object, the present invention provides a method for preparing a modified polydiene, the method comprising the following steps:
[0015] i) preparing a catalyst composite comprising (A) a lanthanide compound, (B) a conjugated diene, (C) an organoaluminum compound, and (D) a halogen-containing component;
[0016] ii) polymerizing a conjugated diene in an organic solvent medium in the presence of the catalyst complex obtained in step i);
[0017] iii) adding a modifier to the polymer when the conversion of the monomer reaches at least 96%, wherein the modifier is a low molecular weight polybutadiene containing terminal alkoxysilane groups;
[0018] iv) terminalizing the polymer product obtained in step iii), introducing an antioxidant and recovering the polymer.
[0019] The technical results include the preparation of polydienes with improved processability and filler distribution in the polymer matrix, wherein rubber compositions based on said polydienes significantly increase the wear resistance of rubber mixtures (Shopper-Schlobach wear volume loss, mm 3 ).
[0020] The modified diene polymer obtained according to the invention is characterized by a Mooney viscosity of 40 to 50 Mooney units, an amount of high molecular weight fraction (HMF 1 million amu) not greater than 3.5% by weight, a branching index characterized by the mechanical loss tangent tgδ (1200%) (measured by thermogravimetry according to ASTM E1131, ISO 11358) of 4.0 to 6.0, and a polydispersity index of 2.1 to 2.5% by weight, a content of 1,4-cis units greater than 96% by weight.
[0021] It is known that the reduction of the Mooney viscosity of the rubber compound allows a reduction in the energy consumption when mixing the rubber with the ingredients, better calendering and extrusion of the rubber composition, and a reduction in the temperature in all steps of its processing, which reduces the possibility of premature vulcanization. In addition, the reduction in the viscosity of the rubber compound allows an increase in the content of fillers in the mixture, thereby reducing its cost. (JS Shashok, AV Kaspyarovich, EPUss. "Principles of compounding formulation of elastomeric compositions" (Russian), 2013. - Page 98)
[0022] Another important indicator is the Payne effect, which reflects the presence of bonds and the strength of interactions between filler particles in a rubber composition. It is known that the quality of rubber depends directly on the degree of filler dispersion in the rubber matrix, which in turn defines the manufacturing time of the rubber composition.
[0023] Achieving a high degree of filler dispersion is quite difficult and one approach to solving this problem has been to propose introducing low molecular weight polybutadiene containing terminal alkoxysilane groups into the diene polymer, thereby creating a strong chemical bond to the filler, as evidenced by low values of the Payne effect.
[0024] According to the present invention, the low molecular weight polybutadiene containing terminal alkoxysilane groups is represented by the general formula (1):
[0025]
[0026] Where R represents a linear or branched C1-C 10 The alkyl group is preferably a hydrocarbon group of C1-C4 alkyl, and n is an integer of 1 to 3.
[0027] According to the invention, a low molecular weight polybutadiene having a molecular weight of 1500 g / mol to 50000 g / mol is used. The increase in molecular weight causes an increase in the dynamic viscosity (MPa*s) of the modifier, wherein there are limitations in the solubility of the polymer, which complicates its introduction in the modification step. The characteristics of the commercially available low molecular weight polybutadiene containing terminal alkoxysilane groups used are shown in Table 1.
[0028] According to the present invention, the process for preparing modified diene polymers comprises several steps, namely: preparing a catalyst complex, polymerizing dienes using the aforementioned complex, introducing a modifier when a conjugated diene conversion equal to 96% and greater is achieved.
[0029] The catalyst composite used in the process according to the invention comprises a lanthanide-containing compound, an organoaluminum compound and a halogen-containing component. The lanthanide-containing compound comprises at least one lanthanide atom: neodymium, lanthanum, cerium, praseodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium. Preference is given to using neodymium compounds.
[0030] The lanthanide-containing compound is: a carboxylate, an organic phosphate (particularly, an alkyl phosphate and an aryl phosphate), an organic phosphonate (particularly, an alkyl phosphonate and an aryl phosphonate), an organic phosphinate (particularly, an alkyl phosphinate and an aryl phosphinate), a carbamate, a dithiocarbamate, a xanthate, a β-diketonate, a halide, a halide oxide, a lanthanide alcoholate, or a mixture thereof, but is not limited thereto.
[0031] Lanthanide carboxylates include formates, acetates, acrylates, methacrylates, valerates, gluconates, citrates, fumarates, lactates, maleates, oxalates, 2-ethylhexanoates, neodecanoates, naphthenates, stearates, oleates, benzoates, and picolinates.
[0032] The lanthanide organophosphates are dibutyl phosphate, diphenyl phosphate, dihexyl phosphate, diheptyl phosphate, dioctyl phosphate, bis(1-methylheptyl) phosphate, bis(2-ethylhexyl) phosphate, didecyl phosphate, didodecyl phosphate, neodymium, bis(n-nonylphenyl) phosphate, butyl(2-ethylhexyl) phosphate, tris[dibutyl phosphate], tris[dipentyl phosphate], tris[dioctyl phosphate], tris[bis(2-ethylhexyl) phosphate], tris[bis(1-methylheptyl) phosphate], tris[bis(p-nonylphenyl) phosphate], tris[butyl(2-ethylhexyl) phosphate], tris[(1-methylheptyl)(2-ethylhexyl) phosphate] and tris[(2-ethylhexyl)(p-nonylphenyl) phosphate].
[0033] Organic phosphonates include butylphosphonate, pentylphosphonate, hexylphosphonate, heptylphosphonate, octylphosphonate, (1-methylheptyl)phosphonate, (2-ethylhexyl)phosphonate, decylphosphonate, dodecylphosphonate, octadecylphosphonate, oleylphosphonate, phenylphosphonate, (n-nonylphenyl)phosphonate, butyl (butylphosphonate), pentyl (pentylphosphonate), hexyl (hexylphosphonate), heptyl (heptylphosphonate), octyl (octylphosphonate), (1-methylheptyl) ((1-methylheptyl) phosphonate), (2-ethylhexyl) ((2-ethylhexyl) phosphonate) ), decyl (decylphosphonate), dodecyl (dodecylphosphonate), octadecyl (octadecylphosphonate), oleyl (oleylphosphonate), phenyl (phenylphosphonate), (n-nonylphenyl)((n-nonylphenyl)phosphonate), butyl ((2-ethylhexyl)phosphonate), (2-ethylhexyl)(butylphosphonate), (1-methylheptyl)((2-ethylhexyl)phosphonate), (2-ethylhexyl)((1-methylheptyl)phosphonate), (2-ethylhexyl)((n-nonylphenyl)phosphonate) and (p-nonylphenyl)((2-ethylhexyl)phosphonate).
[0034] The organic phosphinates include butylphosphinate, amylphosphinate, neohexylphosphinate, heptylphosphinate, octylphosphinate, (1-methylheptyl)phosphinate, (2-ethylhexyl)phosphinate, decylphosphinate, dodecylphosphinate, octadecylphosphinate, oleylphosphinate, phenylphosphinate, (n-nonylphenyl)phosphinate, dibutylphosphinate, diamylphosphinate, dihexylphosphinate, diheptylphosphinate, dioctylphosphinate Phosphinate, bis(1-methylheptyl)phosphinate, bis(2-ethylhexyl)phosphinate, tris[bis(2-ethylhexyl)phosphate], didecylphosphinate, didodecylphosphinate, dioctadecylphosphinate, dioleylphosphinate, diphenylphosphinate, bis(n-nonylphenyl)phosphinate, butyl(2-ethylhexyl)phosphinate, (1-methylheptyl)(2-ethylhexyl)phosphinate and (2-ethylhexyl)(n-nonylphenyl)phosphinate.
[0035] Preferably, carboxylates, neodymium organophosphates are used; most preferably, neodymium neodecanoate, neodymium tris[bis-(2-ethylhexyl)phosphate], or mixtures thereof are used because their alkylation is faster and more complete, which increases the activity of the catalyst composite.
[0036] In the present invention, the conjugated diene includes the following: The following are used as the conjugated diene: 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, piperylene, 2-methyl-3-ethyl-1,3-butadiene, 3-methyl-1,3-pentadiene, 2-methyl-3-ethyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-hexadiene, 2-methyl-1,3-hexadiene Diene, 1,3-heptadiene, 3-methyl-1,3-heptadiene, 1,3-octadiene, 3-butyl-1,3-octadiene, 3,4-dimethyl-1,3-hexadiene, 4,5-diethyl-1,3-octadiene, phenyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2,3-di-n-propyl-1,3-butadiene, 2-methyl-3-isopropyl-1,3-butadiene. 1,3-butadiene and isoprene are most preferably used. The introduction of conjugated dienes is not a mandatory step in the preparation of the catalyst composite, but its presence will significantly increase the activity of the catalyst.
[0037] As the organoaluminum compound (which is the alkylating agent), the following are used: trialkylaluminum, triphenylaluminum or dialkylaluminum hydride, alkylaluminum dihydride, in particular, trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-tert-butylaluminum, triphenylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride Aluminum hydride, diisobutylaluminum hydride, dihexylaluminum hydride, diisohexylaluminum hydride, dioctylaluminum hydride, diisooctylaluminum hydride, phenylethylaluminum hydride, phenyl-n-propylaluminum hydride, phenylisopropylaluminum hydride, phenyl-n-butylaluminum hydride, phenylisobutylaluminum hydride, benzylethylaluminum hydride, benzyl-n-butylaluminum hydride, benzylisobutylaluminum hydride, benzylisopropylaluminum hydride and the like.
[0038] Preferably, alkylaluminum, alkylaluminum hydride, or a mixture thereof is used. Most preferably, triethylaluminum, triisobutylaluminum, diisobutylaluminum hydride, or a mixture thereof is used.
[0039] As the halogen-containing component in the catalyst composite, there can be used aluminum or tin organohalogen compounds, for example dimethylaluminum chloride, diethylaluminum chloride, diisobutylaluminum chloride, dimethylaluminum bromide, diethylaluminum bromide, diisobutylaluminum bromide, dimethylaluminum fluoride, diethylaluminum fluoride, diisobutylaluminum fluoride, dimethylaluminum iodide, diethylaluminum iodide, diisobutylaluminum iodide, methylaluminum dichloride, ethylaluminum dichloride, methylaluminum dibromide The invention also includes but is not limited to: trimethyltin chloride, trimethyltin bromide, triethyltin chloride, triethyltin bromide, di-tert-butyltin dichloride, di-tert-butyltin dibromide, dibutyltin dichloride, dibutyltin dibromide, tributyltin chloride and tributyltin bromide, or a mixture thereof.
[0040] Preference is given to using ethylaluminum sesquichloride, ethylaluminum dichloride, diethylaluminum chloride, or a mixture thereof as the halogen-containing component.
[0041] According to the proposed process, the polymerization solvent is an inert organic solvent, which can be used alone or in a mixture with: other aliphatic hydrocarbons, in particular such as butane, pentane, hexane, heptane; alicyclic hydrocarbons, i.e. cyclopentane, cyclohexane; monoolefins, such as 1-butene, 2-butene, or mixtures thereof; aromatic hydrocarbons, in particular such as benzene, toluene and xylene.
[0042] Most preferably, a hydrocarbon solvent is used as solvent, which is a mixture of cyclohexane:hexane or cyclohexane:nefras (industrial hexane-heptane fraction of paraffins, dearomatized catalytic reformed gasoline with a boiling temperature of (65°C to 75°C), in a ratio of (30 to 55)÷(70 to 45)).
[0043] According to the present invention, polymerization is carried out using a catalyst complex, which comprises (A) a lanthanide compound, (B) a conjugated diene, (C) an organoaluminum compound and (D) a halogen-containing component in a molar ratio of (A):(B):(C):(D) equal to 1:(5 to 30):(8 to 30):(1.5 to 3.0), wherein the mole number of the lanthanide compound (A) is taken based on the mole of the lanthanide, and the mole number of the halogen-containing component (D) is taken based on the mole of the halogen.
[0044] The preferred molar ratio of the components of the catalyst composite (A):(B):(C):(D)=1:(5 to 20):(8 to 20):(1.8 to 2.8).
[0045] The most preferred molar ratio of the components of the catalyst composite (A):(B):(C):(D)=1:(10 to 15):(10 to 15):(2.1 to 2.5).
[0046] The preparation of modified diene polymers is carried out in a hydrocarbon solvent medium by a periodic or continuous process. The process includes supplying a hydrocarbon feed consisting of a monomer and a solvent and a catalyst complex premixed with the solvent into a polymerization vessel (reactor / autoclave), wherein the complex comprises a lanthanide compound, a conjugated diene, an organoaluminum compound and a halogen-containing component (preferably a halogen-containing organic compound). Typically, the concentration of the monomer in the solvent is 7% to 12% by weight, with a preferred concentration of 9% to 10%. A concentration less than 7% reduces the energy efficiency of the process, and a monomer concentration greater than 12% increases the viscosity of the polymer solution, which causes difficulties during transportation, spraying, aggregation, further processing, etc., thereby causing high energy consumption when separating and drying rubber.
[0047] The process of preparing a catalyst complex (CC) comprises introducing an organoaluminum compound (most preferably triisobutylaluminum, triethylaluminum, diisobutylaluminum hydride, or a mixture thereof) into a solution of a lanthanide compound (most preferably neodecanoate or tris[bis(2-ethylhexyl)neodymium phosphate), a conjugated diene (most preferably 1,3-butadiene) in an aliphatic solvent, aging the resulting mixture at a temperature of 23±2° C. for 1 to 20 hours, then adding a halogen-containing component (most preferably ethylaluminum sesquichloride, ethylaluminum dichloride, diethylaluminum chloride, or a mixture thereof) and further aging the catalyst at a temperature of 0 to 100° C., preferably 20 to 50° C. When the temperature is lowered to below 0° C., CC may not be fully aged, and when the temperature is increased to above 50° C., the catalytic activity may decrease and / or the ratio of the average molecular weight (Mw) to the number average molecular weight (Mn) - the polydispersity coefficient may increase. The increase of the latter will negatively affect the final properties of the rubber product, in particular, the wear resistance. The aging time is from 1 minute to several days, and the CC activity may decrease in the future.
[0048] The polymerization time is 1 to 3 hours. When the monomer conversion reaches at least 96%, a modifier which is a low molecular weight polybutadiene containing terminal alkoxysilane groups is applied to the polymer. The modifier is used as a solution in an aliphatic or aromatic solvent. The solution of the branching agent is prepared in advance or is prepared immediately before use.
[0049] The molar ratio of the modifier based on lanthanide is (0.01 to 5): 1, i.e., for every 1 mole of lanthanide, it is acceptable to use 0.01 to 5 moles of modifier. This ratio allows the production of diene polymers with a high content (greater than 96% by weight) of 1,4-cis units, an amount of high molecular weight fraction (HMF) not greater than 3.5% by weight, and a branching coefficient characterized by the mechanical loss tangent tgδ (1200%) in the range of 4.0 to 6.0. An increase in the molar content of the modifier causes excessive branching of the polymer chain, which is undesirable because in this case gelation increases and elastic hysteresis properties deteriorate. The preferred modifier: lanthanide molar ratio is (0.2 to 5): 1, and most preferably (0.4 to 1): 1. In the case of using an amount less than 0.01 relative to the lanthanide, the improved properties claimed for the polymer are not achieved: the resulting rubber has a linear structure; it is a known fact that branched polymers are better processed than linear polymers. Supplying the modifier in an amount of more than 5 moles relative to 1 mole of the lanthanide element not only increases the cost of the final product but also causes strong crosslinking of the polymer, which may adversely affect the plastoelastic properties, thus causing problems for separation of the polymer and its processing.
[0050] Functional alkoxysilane groups react with reactive terminal fragments of diene polymers. The modification process is carried out at a temperature of 60°C to 90°C for 15 minutes to 5 hours, most preferably 20 minutes to 2 hours. A decrease in temperature will increase the viscosity of the polymer; accordingly, it will be difficult to separate and process it, and the rate of "overgrowth" of the assembly (equipment) will increase. At the same time, the increase in the maximum modification temperature shown may cause a loss of activity of the terminal groups of the polymer chain, thereby reducing the degree of polymer modification, that is, the content of residual modifiers will increase.
[0051] At the end of the modification process, the polymer product is blocked with demineralized water or with ethanol or isopropanol and stabilized with an antioxidant solution measured at 0.2% to 0.6% by weight. The rubber is then isolated by known methods such as steam-vapor degassing and drum drying.
[0052] The Mooney viscosity of the resulting polymer after modification is 40 to 50 Mooney units. The increase of this index to more than 50 Mooney units may cause deterioration of manufacturability during processing, and the decrease of this index to less than 40 units leads to an increase in cold flow, which causes problems during transportation and storage of the polymer (polymer agglomerates "flow", loses its shape, and sticks to packaging). The polydispersity coefficient of the modified diene polymer is most preferably 2.1 to 2.5, and the content of 1,4-cis units is greater than 96% by weight. The increase in molecular weight distribution and the decrease in the mass fraction of 1,4-cis units may cause deterioration of mechanical properties and wear resistance. An HMF content of no more than 3.5% by weight is most preferred because the increase in this index may cause gelation of the polymer.
[0053] The invention also relates to a rubber composition. The formulation of the components of the rubber compound is determined by the use of the product, operating conditions and technical requirements, production process and other aspects.
[0054] The rubber production process consists in mixing the rubber with the ingredients in special mixers or on rollers, cutting and chopping the semi-finished products from the rubber (the shape and size depend on the planned future use of the rubber obtained and, in particular, the planned testing methods) and vulcanizing the semi-finished products obtained in special devices (presses, autoclaves, vulcanizers, etc.).
[0055] The rubber compositions comprising the obtained diene polymers are prepared according to a standard recipe (ASTM D3189 recipe, Table 3) and are characterized by improved processability as evidenced by a low Mooney viscosity of the rubber mixture and by improved filler distribution in the rubber (Payne effect). DETAILED DESCRIPTION
[0056] Next, embodiments of the present invention will be described. It should be noted that embodiments of the present invention are not limited to the presented examples, and the same effects can be achieved using other embodiments that do not exceed the essence of the claimed invention.
[0057] Description of the test methods used to evaluate the properties of polymers produced by the claimed process.
[0058] 1. The conversion percentage is determined by a gravimetric method based on the following: separating the polymer from the reaction medium by precipitating the polymer from the polymerization product with ethanol; drying the separated polymer; calculating the polymer mass fraction in the polymerization product and directly calculating the conversion by calculating the ratio of the polymer mass fraction in the polymerization product to the feed mass fraction in the solvent.
[0059] 2. The microstructure of the polymer chains is determined by IR spectroscopy using an MDTIR (multiple disturbed total internal reflection) accessory with a ZnSe crystal according to a proprietary technique. The method is based on recording the IR spectrum of the sample to be analyzed on an infrared Fourier spectrometer using an MDTIR (multiple disturbed total internal reflection) accessory and further measuring the maximum values of the optical density for the following analytical absorption bands: for 740 cm -1 1,4-cis unit at 967 cm -1 1,4-trans unit at 910 cm -1 The IR spectrometer has been calibrated against industrial standard samples of polybutadiene microstructures, where the mass fraction of isomeric units is given by 1 H and 13 C NMR spectroscopy.
[0060] 3. The molecular weight characteristics of the rubber are determined by gel permeation chromatography using a gel chromatograph "Breeze" with a refractometer from the company "Waters" according to a proprietary technique. The rubber sample is dissolved in freshly distilled tetrahydrofuran, the mass concentration of the polymer in the solution is 2 mg / ml, and a universal calibration is performed based on polystyrene standards. The Mark-Kuhn-Houwink constants for diene polymers (K=0.000457, α=0.693) are used for calculation. Determination conditions:
[0061] - A set of 4 high-resolution columns (length 300 mm, diameter 7.8 mm) HR3, HR4, HR5, HR6 filled with styrene gel, which allow the analysis of molecular weights from 500 a.mu to 1×10 7 polymers of amu;
[0062] -The solvent is tetrahydrofuran, and the flow rate is 1cm 3 / minute;
[0063] - The temperature of the thermostat of the column and the refractometer was 30°C.
[0064] 4. The Mooney viscosity (ML1+4 at 100°C) of rubber and rubber compositions was determined on a Mooney MV2000 viscometer according to ASTM D 1646-07.
[0065] 5. The elastic component of the complex dynamic shear modulus G' (kPa), which allows the evaluation of the filler distribution in the rubber mixture and the silanization of the filler, is measured on a rubber processability analyzer RPA-2000 from the company "Alpha Technologies" in the deformation range from 1% to 450% at 0.1 Hz and 100° C. The difference between the cumulative moduli at deformation amplitudes of 1% and 50% - ΔG' = (G'1% - G'43%) - Payne effect.
[0066] 6. Scuff resistance on regenerable surfaces was evaluated according to National Standard 23509 (Method B) on an ABRASION CHECK "Gibitre Instruments" abrasive.
[0067] 7. The branching index (mechanical loss tangent tgδ (1200%)) was determined on a rubber processability analyzer RPA-2000 from the company "Alpha Technologies": the change in tgδ was evaluated under variable amplitude excitation: amplitude range 0% to 1200%, frequency 0.1 Hz, temperature 100°C.
[0068] Example 1 (Prototype)
[0069] The polymerization of butadiene (BD) is carried out in a hydrocarbon solvent in the presence of a catalyst complex prepared based on neodymium (Nd) versatate, followed by the addition of an alkylating agent (i.e., diisobutylaluminumhydride (DIBAH)) and a halogen donor (i.e., diethylaluminum chloride (DEAC)). The amount of neodymium versatate (NdV3) is 2.8 mmol Nd per 1 kg BD, DIBAH is an 8-fold molar excess relative to Nd, and DEAC is a 3-fold molar excess. The polymerization is carried out in a 20-liter reactor equipped with a mixing device and a jacket for heat removal. The polymerization process lasts for 90 minutes. After the polymerization is completed, 2 liters of polymer are extracted from the reactor, and the monomer conversion is 98%. 0.06% by weight of a phenolic antioxidant (Irganox 1520) is added to the selected aliquot. The solvent is removed and ground at a temperature of 80°C. The molecular weight characteristic (MWC) obtained by GPC and the branching coefficient expressed as the mechanical loss tangent tgδ (1200%) were determined in the selected aliquots. A linear polymer with a Mooney viscosity of 35 Mooney units was obtained. At a temperature of 90°C, a solution of maleated polybutadiene Ricon 130 MA 8 in a hexane mixture (solution concentration of 0.15 mol / l) in an amount of 1.2 mol per 1 mol of Nd was supplied to the residual polymer product in the reactor. After 10 minutes, a primary antioxidant (Irganox 565) and a secondary antioxidant (TNPP) were added, and the resulting modified polymer was taken out. The Mooney viscosity of the modified polymer was 43 Mooney units, and the branching coefficient tgδ1200%=5.567, i.e. a branched polymer was obtained (Table 1). The content of the polymer in the rubber compound was also tested according to the ASTM 3189 formula (Table 3), and the test results are shown in Table 4.
[0070] Example 2 (Comparison, no modifier added)
[0071] 2.3 g (1.4 mmol) of neodymium neodecanoate as a solution in hexane with a concentration of 8.9%, 40 ml of aliphatic solvent were placed in a Schlenk flask with a volume of 250 ml and stirred for 10 minutes at 23° C. using a magnetic stirrer. Then 3.6 g of butadiene (BD) in the form of a solution with a concentration of 22.4% by weight were introduced into the flask. The molar ratio of BD / Nd=10.
[0072] After stirring at 23° C. for 15 minutes, 12.2 ml of DIBAH solution with a concentration of 1.18 mol / l was supplied to the flask and stirred for 30 minutes. The molar ratio of DIBAH / Nd = 10. Then, 5.8 ml of EASC solution with a concentration of 0.73 mol / L was introduced, and the molar ratio of Cl / Nd = 3.0. Then, the solvent was introduced into the composite to make the solution volume 100 ml, which was stirred for 10 minutes and kept at 20° C. to 23° C. for 20 hours to form it.
[0073] The polymerization was carried out in a reactor with a volume of 10 L equipped with a stirrer and a jacket for heat removal. The temperature of the polymerization reaction was 95° C. to 100° C. The duration of the process was 2 hours.
[0074] When the monomer conversion rate reached 96%, a polymerization inhibitor was supplied, a phenolic antioxidant was added, and degassing and drum drying were performed. The properties of the obtained polymer are shown in Table 2. The samples were also tested according to the formulation ASTM 3189 of the rubber composition (Table 3), and the test results are shown in Table 4.
[0075] Example 3
[0076] Example 3 is similar to Example 2, except that when 96% monomer conversion is achieved, a modifier, low molecular weight polybutadiene Polyvest EP-ST-E 60, having a molecular weight of 3200 g / mol and containing terminal triethoxysilane groups, is supplied to the polymerized product. The low molecular weight polybutadiene is applied in the form of a solution in nefras at a molar ratio of 0.6 relative to neodymium.
[0077] The properties of the obtained polymer are shown in Table 2. The samples were also tested according to the formulation ASTM 3189 of the rubber composition (Table 3), and the test results are shown in Table 4.
[0078] Example 4
[0079] Example 4 is similar to Example 2, except that diethylaluminum chloride (DEAC) is used as the chlorinating agent in the catalyst composite formulation, and the Cl / Nd molar ratio is 2.5. Low molecular weight polybutadiene is applied as a modifier at a molar ratio of 0.2 relative to neodymium.
[0080] The properties of the obtained polymer are shown in Table 2. The samples were also tested according to the formulation ASTM 3189 of the rubber composition (Table 3), and the test results are shown in Table 4.
[0081] Example 5
[0082] Example 5 is similar to Example 3, except that a low molecular weight polybutadiene Polyvest EP-ST-E 100 having a molecular weight of 3250 g / mol as a modifier is applied at a molar ratio of 1.0 relative to neodymium.
[0083] The properties of the obtained polymer are shown in Table 2. The samples were also tested according to the formulation ASTM 3189 of the rubber composition (Table 3), and the test results are shown in Table 4.
[0084] Example 6
[0085] Example 6 is similar to Example 5, except that gadolinium tert-carbonate is used as the lanthanide salt, 2-methylbuta-1,3-diene-isoprene is used as the modifier, and the molar ratio of polyisoprene to gadolinium is 5.0. The molecular weight of the low molecular weight polybutadiene Polyvest EP-ST-E 80 used as the modifier is 3250 g / mol.
[0086] The properties of the obtained polymer are shown in Table 2. The samples were also tested according to the formulation ASTM 3189 of the rubber composition (Table 3), and the test results are shown in Table 4.
[0087] Example 7
[0088] Example 7 is similar to Example 6, except that neodymium tris-[bis-(2-ethylhexyl)phosphate] is used as the lanthanide salt, and the molar ratio of Cl / Nd is 2.5. Low molecular weight polybutadiene Polyvest EP-ST-E 80 is used at a molar ratio of 5.0 relative to neodymium.
[0089] The properties of the obtained polymer are shown in Table 2. The samples were also tested according to the formulation ASTM 3189 of the rubber composition (Table 3), and the test results are shown in Table 4.
[0090] Example 8
[0091] Example 8 is similar to Example 7, except that neodymium tris-[(2-ethyl)hexanoate] is used as the lanthanide salt, and diethylaluminum chloride (DEAC) is used as the chlorinating agent; the molar ratio of Cl / Nd is 2.3. A low molecular weight polybutadiene Polyvest EP-ST-E 80 is used at a molar ratio of 0.01 relative to neodymium.
[0092] Example 9 (Comparative)
[0093] Example 9 is similar to Example 5, except that isoprene is selected as the conjugated diene, diethylaluminum chloride is selected as the halogen-containing component, the Cl / Nd molar ratio is 2.2, and low molecular weight polybutadiene Polyvest EP-ST-E 60 is used at a molar ratio of 8.0 relative to neodymium.
[0094] Example 10
[0095] Example 10 is similar to Example 9, but the difference is that 1,3-butadiene is selected as the conjugated diene, EASC is selected as the halogen-containing component, the molar ratio of Cl / Nd is 2.5, and the molar ratio of low molecular weight polybutadiene Polyvest EP-ST-E 60 to neodymium is 5.0.
[0096] Table 1 Characterization of the liquid rubber used according to the present invention
[0097]
[0098] *-Silane-functionalized low molecular weight (liquid) polybutadiene rubbers with different degrees of functionalization (silanization).
[0099] Polyvest EP-ST-E 60-60%-Silanized
[0100] Polyvest EP-ST-E 80-80%-Silanized
[0101] Polyvest EP-ST-E 100-100%-Silanized
[0102] Table 2 Polymer properties
[0103]
[0104]
[0105] Continued Table 2.
[0106]
[0107]
[0108] A list of abbreviations is shown in Table 2:
[0109] NdP3-neodymium tris-[bis-(2-ethylhexyl) phosphate]
[0110] NdV3-Nd neodecanoate
[0111] GdV3-gadolinium tert-carbonate
[0112] NdEh3-neodymium tris-[(2-ethyl)hexanoate]
[0113] DEAC-Diethylaluminum chloride
[0114] EASC-Ethylaluminum Sesquichloride
[0115] Table 3 Formulation of rubber composition (ASTM 3189)
[0116]
[0117]
[0118] Table 4 Plastic-elastic properties of rubber compositions
[0119]
[0120] *RPA 2000 viscoelastic properties of rubber compositions [100°C; frequency: 0.1 Hz; strain sweep: 1% to 300%]
[0121] As can be seen from Table 2, the degree of branching of the polymer according to the embodiment of the prototype is lower than the degree of branching of the polymer according to the present invention. The degree of branching affects the processability of the polymer in the rubber mixing stage and the use of the rubber comprising such a polymer. According to the Mooney viscosity of the rubber composition, processability is assessed, according to embodiments of the present invention, the Mooney viscosity (table 4) is significantly lower than the Mooney viscosity in the prototype and the comparative example, which shows good processability. The benefit of using the rubber comprising the polymer obtained can be evaluated by the Shopper-Schlobach wear index (table 4)-in embodiments according to the present invention, wear is much lower.
[0122] At the same time, other parameters such as Mooney viscosity ML (1+4), the content of 1,4-cis units and the amount of high molecular weight fractions are at the same level as each other. It is also obvious that the increase in the molar content of the modifier leads to high branching of the polymer (Example 9): the branching index tgδ (1200%) is significantly lower than 4.0, which leads to the formation of insoluble polymers from which it is difficult to obtain molecular weight characteristics.
Claims
1. A method for preparing a modified polydiene, comprising the following steps: i) preparing a catalyst composite, the catalyst composite comprising (A) Lanthanide compounds, (B) conjugated dienes, (C) organoaluminum compounds, and (D) halogen-containing components; ii) polymerizing a conjugated diene in an organic solvent in the presence of the catalyst complex obtained in step i); iii) introducing a modifier into the polymer when the conversion of the monomers reaches at least 96%, wherein the modifier is a low molecular weight polybutadiene having a molecular weight of 1500 g / mol to 50000 g / mol and comprising terminal alkoxysilane groups; iv) terminalizing the polymer product obtained in step iii), introducing an antioxidant and recovering the polymer, wherein the molar ratio of the modifier to the lanthanide element is (0.01 to 5):
1.
2. The method according to claim 1, characterized in that the molar ratio of the modifier to the lanthanide is (0.2 to 5):1, wherein the molar number of the lanthanide compound (A) is taken based on the mole of the lanthanide.
3. The method according to claim 1, characterized in that the molar ratio of the modifier to the lanthanide is (0.4 to 1):1, wherein the molar number of the lanthanide compound (A) is taken based on the mole of the lanthanide.
4. The method according to claim 1, characterized in that the modification process is carried out for 15 minutes to 5 hours.
5. The method according to claim 1, characterized in that the modification process is carried out for 20 minutes to 2 hours.
6. The method according to claim 1, characterized in that the molar ratio of the components of the catalyst composite (A): (B): (C): (D) is 1: (5 to 30): (8 to 30): (1.5 to 3.0), wherein the molar number of the lanthanide compound (A) is taken based on the molar number of the lanthanide, and the molar number of the halogen-containing component (D) is taken based on the molar number of the halogen.
7. The method according to claim 1, characterized in that the molar ratio of the components of the catalyst composite (A): (B): (C): (D) is 1: (5 to 20): (8 to 20): (1.8 to 2.8), wherein the molar number of the lanthanide compound (A) is taken based on the molar number of the lanthanide, and the molar number of the halogen-containing component (D) is taken based on the molar number of the halogen.
8. The method according to claim 1, characterized in that the molar ratio of the components of the catalyst composite (A): (B): (C): (D) is equal to 1: (10 to 15): (10 to 15): (2.1 to 2.5), wherein the molar number of the lanthanide compound (A) is taken based on the molar number of the lanthanide, and the molar number of the halogen-containing component (D) is taken based on the molar number of the halogen.
9. The process according to claim 1, characterized in that the following are used as conjugated dienes: 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, piperylene, 2-methyl-3-ethyl-1,3-butadiene, 3-methyl-1,3-pentadiene, 2-methyl-3-ethyl-1,3-pentadiene, 1,3-hexadiene, 2-methyl-1,3-hexadiene, 1,3-heptadiene, 3-methyl-1,3-heptadiene, 1,3-octadiene, 3-butyl-1,3-octadiene, 3,4-dimethyl-1,3-hexadiene, 4,5-diethyl-1,3-octadiene, phenyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2,3-di-n-propyl-1,3-butadiene, 2-methyl-3-isopropyl-1,3-butadiene.
10. The process according to claim 1, characterized in that 1,3-butadiene and isoprene are used as the conjugated dienes.
11. A modified polydiene obtained by the process according to claim 1, characterized in that the Mooney viscosity is between 40 and 50 Mooney units, the amount of high molecular weight fraction HMF exceeding 1 million amu is not greater than 3.5% by weight, and the branching index expressed as mechanical loss tangent tgδ 1200% is equal to 4.0 to 6.
0.
12. A modified polydiene obtained by the process according to claim 1.
13. A rubber compound comprising a polydiene according to claim 11 or claim 12.
Citation Information
Patent Citations
Natural rubber mixture with improved low temperature flexibility
EP2082899A1
Process for producing modified low-molecular rubers
SU1028681A1
Rubber composition containing a terminally-functionalized low molecular weight diene polymer
US5430095A
Low molecular weight high-cis polybutadienes and their use in high molecular weight-low molecular weight high-cis polybutadiene blends
US6437205B1
Process for the preparation of low branch content polybutadiene
US7112632B2